Abundance, spatial, and temporal distribution of shorebirds (Order: Charadriiformes) at Marismas Nacionales, Mexico - Mendoza, Luis Francisco (2019)
Northwest Mexico is an important region for shorebirds associated with an extensive series of wetlands. However, for many of these wetlands, basic information about shorebirds communities like abundance, population trends, and richness are limited. Currently, wintering and stopover sites are critical for conservation because many populations of shorebirds have declined in the last decades. Marismas Nacionales (MN) is an important tropical wetland with a dynamic ecosystem and where shorebirds studies are limited to few wintering aerial and ground surveys. Our goals were analyzing shorebirds abundance and spatial and temporal distribution patterns in 2010-2011 season. We selected eight monitoring sites from two prospective visits to the study area. We observed shorebirds monthly between November 2010 and June 2011 to analyze richness and abundance patterns by site and month. Additionally, we describe specific spatial and temporal distribution for dominant species. A total of 27 shorebirds species and one genus, with a minimum global abundance of 136 236 individuals. Shorebird abundance at MN is among the most important in the region with around 10 % of total abundance in northwest Mexico; therefore, MN is a priority conservation site for this group of birds. Additionally, MN presents a suitable habitat for breeding of some species of shorebirds such as Snowy and Wilson’ Plover, Killdeer, Northern Jacana, Black-necked Stilt and Pacific American Oystercatcher. Dominant species were Western Sandpiper (33.5 % of total in MN), American Avocet (31 %) and Dowitchers (17 %). These taxa are very common in others wetlands in Northwest Mexico region. Spatially, shorebirds were distributed in three sites: Chumbeño lagoon (37 % of abundance total), Las Garzas-Chihuin lagoons (24.2 %) and La Polca lagoon (24 %). The less used sites by shorebirds are located in the southern part of MN. Our results update MN information and can help to establish monitoring programs in the area.